Personal Watercraft Remote Control Communication Fault Detection - Ádám Titrik (Engineering Proceedings, 2024)
Hydroflight is a watersport where the user utilizes a waterjet-propelled backpack to fly over water. These backpacks are usually powered by purpose-built equipment but can also be propelled by personal watercraft. To have full control over movement during hydroflight, the user needs to adjust the throttle of the watercraft, which is commonly performed by converting the system to remote-controlled operation. However, care should be taken during conversion to ensure safe operation and avoid harm to the user. This paper presents a failure analysis of sudden safety mode activation on a personal watercraft converted to remote control for hydroflight applications, as well as actions taken to avoid full shutdown in the case of communication loss, without compromising user safety.